The positive effect of social support on psychological distress among Chinese lung cancer patients: The mediating role of self‐esteem - Xu Tian; Yanfei Jin; Hui Chen; Ling Tang; Maria F. Jiménez‐Herrera (Wiley, 2021)
Abstract Aim To investigate the effect of social support on psychological distress among Chinese lung cancer patients and clarify the mediating role of self‐esteem. Design A cross‐sectional descriptive correlational survey of 441 Chinese lung cancer patients was designed. Methods Self‐esteem was supposed to play a mediating role in the association between social support and psychological distress. We collected demographic information, the Distress Thermometer, Multidimensional Scale of Perceived Social Support and Rosenberg Self‐Esteem Scale. Results Our revised model demonstrated an acceptable fit to the data (χ2 = 37.489, comparative fit index (CFI) = 0.965, Tucker‐Lewis index (TLI) = 0.926, root mean square error of approximation [RMSEA] = 0.099). Social support had a direct effect on self‐esteem and psychological distress, and self‐esteem had also a direct effect on psychological distress. Meanwhile, self‐esteem also partially mediated the relationship between social support and psychological distress among Chinese lung cancer patients.